HIV-Tat and vascular endothelium: implications in the HIV associated brain, heart, and lung complications - Chandran, Sivasankar; Adler, Morgan; Chen, Ling; Kaur, Sandeep; Dhillon, Navneet K. (Frontiers in Immunology, 2025)
Following the advent of antiretroviral therapy (ART), neurological, cardiovascular, and pulmonary comorbidities emerged as major challenges in treating non-infectious complications in people living with HIV. Despite effective ART, HIV viral proteins can persist in circulation even in individuals with negligible viral loads, potentially contributing to cellular and tissue-level stress, inflammation, and related health complications. Most of the HIV protein: Tat (Trans activator of Transcription), expressed in HIV-infected cells, is actively secreted and exerts its pathological effects on non-infected cells, particularly impacting the vascular endothelium. This review focuses on the role and the underlying mechanisms of HIV-Tat in promoting endothelial dysfunction across the cardiovascular, pulmonary, and brain vasculature. Additionally, we discuss how HIV-Tat interacts synergistically with drugs of abuse to exacerbate endothelial damage. Importantly, the vascular damage caused by Tat is not fully mitigated by HAART, necessitating further mechanistic investigations and targeted therapeutic interventions. Additionally, cessation of drug abuse is indispensable for improving clinical outcomes and restoring vascular health in people living with HIV.